2012
DOI: 10.1111/j.1439-0418.2012.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of the relative attractiveness of enriched ginger root oil (EGO)lure and trimedlure for African Ceratitis species (Diptera: Tephritidae)

Abstract: The males of some fruit flies (Diptera: Tephritidae) are known to be attracted to specific parapheromones. The trapping results between trimedlure (TML) and enriched ginger root oil (EGOlure) were compared at two experimental sites in Morogoro (Central Tanzania) for a period of 12 weeks co‐inciding with the main citrus season. Both attractants captured a comparable diversity of fruit flies, except that EGOlure also attracted fruit flies, such as Ceratitis cosyra, not normally found in TML‐baited traps. Both EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
3
15
1
Order By: Relevance
“…Although EGO Pheroluredid not capture any B. dorsalis, EGO Pherolure (new device) and EGO Pherolure + Permethrin (new device) captured nine and eight B. dorsalis males, respectively. These findings are in accordance with Mwatawala et al [21], who also reported a low response to enrich ginger oil-containing products.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although EGO Pheroluredid not capture any B. dorsalis, EGO Pherolure (new device) and EGO Pherolure + Permethrin (new device) captured nine and eight B. dorsalis males, respectively. These findings are in accordance with Mwatawala et al [21], who also reported a low response to enrich ginger oil-containing products.…”
Section: Discussionsupporting
confidence: 83%
“…Enriched ginger oil (EGO) is a source of alpha-coapane and is known to be an attractant for Ceratitis species [6,20,21]. It also has a male enhancing component, because exposure to its aroma increases the mating success of males [22][23][24].…”
mentioning
confidence: 99%
“…In a previous study, the catches of Ceratitis rosa and Ceratitis capitata by EGO lure were equal or superior to TM (Mwatawala et al 2013). The present study showed that EGO lure is a significantly stronger attractant for the males of Ceratitis rosa , Ceratitis capitata and Ceratitis cosyra .…”
Section: Discussionmentioning
confidence: 74%
“…Remarks while this species was until recently unknown, it has been found in relatively high numbers (up to 400 flies/trap/week) through trapping activities using enriched ginger oil (EGOlure, Insect Science, tzaneen South africa) in central tanzania (Mwatawala et al 2013; referred to as 'C. near cosyra').…”
Section: Unknownmentioning
confidence: 99%